Training and injuries amongst elite female orienteers - Creagh, U.; Reilly, T. (The Journal of Sports Medicine and Physical Fitness, 1998)
BACKGROUND: A study was carried out on the patterns of injury amongst elite female orienteers. METHODS: A retrospective questionnaire was administered which contained questions pertaining to training practices such as quality, quantity and type. This was followed by a section investigating general to specific injury problems, regarding their occurrence and effect on training. Members of various national orienteering squads (elite group; n = 19) and competitors of an elite level in Great Britain (sub-elite group; n = 9) completed these questionnaires. As this was a descriptive study, no intervention was carried out. RESULTS: The sub-elite orienteers trained less than the elite during the off-season (p < 0.01) but there was no significant difference in the distribution and/or likely cause of injuries between the groups. Only 32% of the subjects did their training predominantly on the road while the others ran on either off-road terrain or a mixture. Injuries occurred in 68% of the respondents. Only 4% of them suffered upper body injuries. Ankle injuries were the most common injuries. The proportion of injuries to the knee (16%) and ankle (43%) in orienteers was the reverse of what is normally found in runners. CONCLUSIONS: Orienteers suffer certain sport specific injuries such as ankle sprain. This is likely to be related to their training predominantly on rough surfaces